Persistent Quantitative Vitality of Stem Cell Graft Is Necessary for Stabilization of Functional Brain Networks After Stroke - Green, Claudia; Minassian, Anuka; Vogel, Stefanie; Diedenhofen, Michael; Wiedermann, Dirk; Hoehn, Mathias (Frontiers in Neurology, 2019)
Stem cell treatment after stroke has demonstrated substantial outcome improvement. However, monitoring of stem cell fate in vivo is still challenging and not routinely performed, yet important to quantify the role of the implanted stem cells on lesion improvement; in several studies even mortality of the graft has been reported. Resting state functional magnetic resonance imaging (rs-fMRI) is a highly sensitive imaging modality to monitor the brain-wide functional network alterations of many brain diseases in vivo. Here wWe monitor for three months the functional connectivity changes after intracortical stem cell engraftment in large, cortico-striatal (n=9) and in small, striatal (n=6) ischemic lesions in the mouse brain with noninvasive rs-fMRI on a 9.4T preclinical MRi scanner with GE-EPI sequence. , and Graft vitality is continuously recorded the graft vitality by bioluminescence imaging roughly every 2 weeks after implantation of 300 k neural stem cells. In cortico-striatal lesions, the lesion extension induces graft vitality loss, in consequence leading to a parallel decrease of functional connectivity strength after a few weeks. In small, striatal lesions, the graft vitality is preserved for the whole observation period and the functional connectivity is stabilized at values as in the pre-stroke situation. But even here, at the end of the observation period of three months, the functional connectivity strength is found to decrease despite preserved graft vitality. We conclude that quantitative graft viability is a necessary but not sufficient criterion for functional neuronal network stabilization after stroke. Future studies with even longer time periods after stroke induction will need to identify additional players which have negative influence on the functional brain networks.